Strength Performance of Concrete Using Rice Husk Ash (RHA) as Supplementary Cementitious Material (SCM) - Patah, Dahlia; Dasar, Amry (Journal of the Civil Engineering Forum, 2022)
Rice husk ash (RHA) is an industrial waste obtained from raw material that is processed into ash through the combustion process. It is a solid waste in fine powder form, which contains a large amount of silica and can promote RHA through combustion under certain conditions. Furthermore, it has a high pozzolanic activity due to a large amount of silica, which is a kind of supplementary cementitious material (SCM). According to ASTM C618, RHA has potential as sustainable material that meets the specification of the chemical configuration of pozzolan compound that can be used in cement products and concrete mixing. The use of RHA as SCMs in concrete construction contributes to sustainability and eco-material. Therefore, this study aims to evaluate the application of RHA as SCM on the strength base performance of concrete. The sample was directly collected from the rice field after the natural combusting process without additional treatment, controlled burning temperature, or time. RHA was used as an admixture for cement substitute and the mechanical characteristics were evaluated using a cylindrical concrete specimen made with 100-mm diameter and 200-mm height. After 24-hours, the concrete specimens were demolded and immediately immersed curing in fresh water with uncontrolled laboratory condition until the day of testing. The results showed that RHA with a replacement ratio of 7.5% obtained an optimum compressive strength of 40.65 MPa and 48.79 MPa at 28 and 91 days, respectively. The split tensile test also gave an optimum replacement ratio of RHA is 10% with 4.57 MPa at 28 days. These results provide good input on using RHA as SCM for concrete strength base performance and future sustainable material.